2015
DOI: 10.1074/jbc.m115.667899
|View full text |Cite
|
Sign up to set email alerts
|

Trpm7 Protein Contributes to Intercellular Junction Formation in Mouse Urothelium

Abstract: Background: Transient receptor potential melastatin 7 (Trpm7) is a Ca 2ϩ -permeable channel with a kinase domain that is implicated in cell migration and adhesion. Results: Urothelium-specific Trpm7 knock-out caused immature intercellular junctions, inflammation, and smaller voided volume. Conclusion: Trpm7 contributes to the intercellular junction formation in the urothelium. Significance: These findings might provide the first evidence for the significance of Trpm7 in bladder function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(38 reference statements)
1
14
0
Order By: Relevance
“…21 Another study collecting mouse urothelial cells suggested that down-regulated TRPM7 causes immature intercellular junctions, inflammation, and smaller voided volume. 3 In the present study, TRPM7 was negatively correlated with pollakisuria only in IC patients. We speculated from our result that the barrier function could be disrupted in IC, inducing inflammation and pollakisuria.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…21 Another study collecting mouse urothelial cells suggested that down-regulated TRPM7 causes immature intercellular junctions, inflammation, and smaller voided volume. 3 In the present study, TRPM7 was negatively correlated with pollakisuria only in IC patients. We speculated from our result that the barrier function could be disrupted in IC, inducing inflammation and pollakisuria.…”
Section: Discussionsupporting
confidence: 48%
“…TRPM7 is functionally expressed in mouse urothelial cells, and is thought to act as a mechano‐sensor and/or chemo‐sensor . Another study collecting mouse urothelial cells suggested that down‐regulated TRPM7 causes immature intercellular junctions, inflammation, and smaller voided volume . In the present study, TRPM7 was negatively correlated with pollakisuria only in IC patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Little is known about the mechanisms about bladder activity. Several ion channels such as TRPM7 (30) or PIEZO1 (26) have also been known to be involved in bladder activity. However, pBOO did result in an increase in bladder weight (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…70 TRPM7 has been implicated in the formation of tight junctions in the mouse urinary bladder epithelium. 71 Bladders of inducible urothelium-specific TRPM7 knockout mice displayed submucosal edema and shorter length of tight junctions along the urothelium. Elevated levels of Interleukin-1b and Tumor Necrosis Factor a were also detected in the bladder wall.…”
Section: Other Epitheliamentioning
confidence: 99%